Are there financing constraints for R&D and investment in German manufacturing firms? - Dietmar Harhoff (Zentrum für Europäische Wirtschaftsforschung (ZEW); ZBW – Leibniz Information Centre for Economics, 1996)
Using a newly constructed panel dataset of German enterprises, I estimate R&D and capital investment equations for the time period from 1990 to 1994. Simple accelerator specifications indicate considerable sensitivity of R&D and investment to cash flow for relatively small firms. Much of this effect vanishes already once error-correcting behavior is taken into account, but a significant positive relationship between cash flow and investment remains for relatively small firms. In the case of R&D, weak but significant cash flow persist both for small and large firms. The evidence from Euler equation estimates is not conclusive. The investment Euler equation for large firms appears to perform relatively well and yields results close to those expected under the null hypothesis of no financing constraints. The estimates from the Euler equation for R&D are not informative. Additional evidence from survey data suggests that the cash flow sensitivity of investment in small firms is likely to reflect financing constraints.
Keywords: L10; O31; C23; G30; 330; R&D; investment; financial constraints; firm size; credit rationing